Cigarette price elasticity in Croatia: Analysis of household budget surveys - Željana Aljinović Barać; Paško Burnać; Andrijana Rogošić; Slavko Šodan; Tina Vuko (Journal of Applied Economics, 2021)
This study estimates both conditional and unconditional cigarette price elasticity of quantity demanded in Croatia. Authors use Deaton's method, also known as the Almost Ideal Demand-System (AIDS), to obtain consistent estimates of the cigarette price elasticity on the sample of Croatian households. The data from household surveys (HBS) conducted in Croatia for three periods (2010, 2011 and 2014 year) is provided by the Croatian Bureau of Statistics (CBS). Estimated unconditional cigarette price elasticity is - 1.38 and estimated conditional price elasticity is - 0.63. Simulation of the tax effects shows that rising specific excise tax for 10 percent would result in 2 percent decrease in cigarette consumption while total tax revenues would increase by 1.97 percent. This study provides evidence that the demanded quantity for cigarettes is responsive to their prices. Consequently, this implies that tobacco tax policy can be used as an efficient tool for reducing cigarette consumption in Croatia.
Keywords: 330; Cigarette price; economics; public policy; taxation